Military Caregivers Cornerstones of Support for Our Nation's Wounded, Ill, and Injured Veterans - Tanielian, Terri (RAND Corporation, 2013)
Military caregivers are an essential part of our nation's ability to care for returning wounded warriors. Far too often, their own needs are neglected. The RAND Corporation and the Elizabeth Dole Foundation lay the groundwork to inform policy and program development relative to the needs of military caregivers that often differ from the needs of the general caregiving population.